Dynamic analysis of the diffusion and adsorption of water-miscible and water-immiscible organic vapors in soil - Kalender, M; Akosman, C (Wiley-V C H Verlag Gmbh, 2004)
A dynamic analysis of the diffusion and adsorption of water-miscible volatile organic compounds (methanol and acetone) and water-immiscible volatile organic compounds (benzene and toluene) in a soil pellet has been performed experimentally by using the single pellet moment technique. The experiments were conducted in a one-sided single pellet adsorption cell at a temperature of 30degreesC and varying relative humidities (0, 20, and 40%). The results obtained with dry and wet systems showed that volatile organic tracers were adsorbed reversibly onto the soil. The overall adsorption equilibrium constants of both water-miscible and water immiscible volatile organic compounds decreased with relative humidity. The sorption of water-immiscible VOCs (benzene) onto soil was found to be much less than that of water-miscible VOCs (methanol). The effective diffusivity of water-immiscible volatile organic vapor (benzene) in the soil did not show a considerable change with relative humidity. In contrast, there was an appreciable change in the effective diffusivity for water-miscible VOCs (methanol) with moisture.
Keywords: Single-Pellet Technique; Chlorinated Methanes; Relative-Humidity; Sorption; Clay; Moisture; Temperature